Black bear use of seismic lines in Northern Canada. Issue 2 (21st January 2014) - Tigner, Jesse; Bayne, Erin M; Boutin, Stan
ABSTRACT The development of hydrocarbon resources in northwestern Canada has resulted in a vast network of seismic lines. Seismic lines are a conservation concern because they are believed to alter the use of space by predators and ultimately change predator‐prey relationships. Such changes are believed to be a key factor influencing declines in boreal woodland caribou (Rangifer tarandus caribou). Using remote wildlife cameras, we measured the behavioral response of a known caribou predator, the black bear (Ursus americanus), to seismic lines at 2 spatial scales. At the line scale, we compared black bear use of lines that varied in width and vegetation recovery state to undisturbed forest interior locations. At a 5‐km2 scale, we compared the probability of bear use across a continuum of seismic line density. At both spatial scales, we also tested for an interaction between bear use of seismic lines and use of upland and lowland forest types. Black bears used most types of seismic lines more frequently than undisturbed forest interior and upland forest more than lowland forest. We found no evidence of an interaction between lines and forest type, as the relative difference in seismic line versus forest interior use was the same in lowland and upland forest. At the 5‐km2 scale, we found no evidence of increased use of lowland forest in areas with greater seismic line density. Thus, seismic lines did not appear to increase black bear use of lowland forest types per se. However, bears used seismic lines more than forest interiors, which might alter their ability to locate and capture caribou and other ungulate prey, thereby creating the potential for altered predator‐prey dynamics in landscapes with seismic lines. Bears do not appear to use seismic lines ≤2 m wide more often than the forest interior. We suggest that where new seismic lines are constructed, those seismic lines should be a maximum width of 2 m to reduce the potential for altered predator‐prey dynamics in areas being developed for oil and gas extraction. © 2014 The Wildlife Society.